Richard van der Ross, In Our Own Skins: A Political History of the Coloured People : An important publication on a contested social label (Historia, 2021)
It goes without saying that the label "Coloured" is clouded in controversy. While some embrace it, others loathe it, and under the best of circumstances, it remains good advice to avoid the term altogether. While one is perhaps at liberty in 2016 to completely ignore this description of people of diverse backgrounds, it is impossible for a serious scholar of South African history to deny the political implications of the tag. Many South Africans were classified and administered under the apartheid government as Coloured persons. In this sense, Richard van der Ross delivers an important message about his book in its opening pages when he wrtites: "This book deals with the people of South Africa. It concerns all the people of South Africa, although it deals more specifically with the Coloured people".